Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai Desa Suka Damai Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat - Evita Ratna Sari; Adria Wuri Lastari; Jumisar; Seno Aji (LPPM Universitas Adiwangsa Jambi, 2022)
Management of government resources is a major factor in realizing good service in the public sector. However, in this study, the village apparatus still needs to improve its performance which is closely related to motivation as the reason for the success of the village apparatus's performance. The purpose of this study is to analyze how much work motivation affects the performance of the Suka Damai village apparatus. The types of data used in this study are primary and secondary data. Using a simple analysis method with the SPSS 26 analysis tool. The results of the study showed that work motivation had a positive and significant effect on the performance of the Suka Damai village apparatus. In addition, the R square value or determination coefficient is 0.537 or 53.7 % which means that work motivation has an effect of 53.7 % on the performance variables of the village apparatus and the other 46.3 % is influenced by other factors outside the work motivation variable